Continuous Visual Stimulation Is Associated With Reduced Occipital Brain Temperature Measured By Magnetic Resonance Spectroscopy Thermometry - Abdul Nashirudeen Mumuni; Mohammed Nasir Abubakari (Iranian Journal of Medical Physics)
Introduction: There is paucity of information about the impact of different neuroactivation paradigms on brain temperature changes in functional magnetic resonance spectroscopy (fMRS) studies. Magnetic resonance spectroscopy (MRS) thermometry was used to estimate the pattern of brain temperature changes with single and continuous neuroactivation paradigms. Material and Methods: Single-voxel MRS data was acquired from the visual cortex of four healthy volunteers using the standard spin-echo Point-RESolved Spectroscopy (PRESS) localization sequence synchronized to single and continuous visual stimulation paradigms at 3.0 tesla (T). Blood oxygenation level-dependent (BOLD) effects were estimated from changes in spectral peak height, linewidth, and area. Brain temperature was calculated by substituting the frequency offset of the water peak relative to the N-acetyl aspartate (NAA), creatine (Cr), and choline (Cho) peaks into previously deduced calibration equations for each reference peak. BOLD and temperature changes from baseline were compared by paired t-test at a significance level of p < 0.05. Results: In the single activation paradigm, Cho (p = 0.01) peak height, and NAA (p = 0.01) and Cr (p = 0.02) peak areas showed significant changes without significant brain temperature changes relative to all three peaks (p > 0.05). In the continuous activation paradigm, Cr (p = 0.04) peak width showed significant change, with significant brain temperature changes relative to all three reference peaks (p < 0.05). Conclusion: Brain temperature significantly reduced with continuous visual activation but not with single visual activation paradigms.